Adaptation to Flooding and Mitigating Impacts of Road Construction − a Framework to Identify Practical Steps to Counter Climate Change - Mallick, Rajib B.; Zaumanis, Martins; Frank, Robert (The Baltic Journal of Road and Bridge Engineering, 2015)
Adaptation and mitigation are the two critical actions that are needed to counter the looming threats of climate change on transportation. For roadways, flooding constitutes one of the most important impacts of climate change, and adaptation to build more resilient roadways must be made. For a proper adaptation, the first step is a way to properly assess the vulnerability of roadways to flooding. Road construction impacts the environment negatively through emissions and energy consumption, and a proper way to determine the practical methods to reduce the impact is also necessary. This paper presents a framework to assess the vulnerability of roadways to flooding and evaluate the impact of different changes in construction on energy consumption and emission. Two system dynamics based models were developed and results of the simulations have been presented. Simulation tools for these two models have also been developed and made available on the public domain. The results of the simulation point out the beneficial effects of providing low permeability and dense and thick surface layers to reduce vulnerability to flooding and that of using drier aggregates, reducing heat losses, reduced mix temperatures and extension of pavement lives on the emission and energy consumption during roadway construction.